Exploring Acapella Therapy for Enhancing Pulmonary Parameters in Bronchiectasis patients: A Scoping Review - Pinki, Pinki; Aditi, Aditi; Nagpal, Lakshya (Journal of Neonatal Surgery, 2025)
Objective: To investigate the impact of acapella therapy on pulmonary function, sputum volume, and health-related quality of life (HRQOL) in individuals with bronchiectasis, supported by evidence-based research. Methods: This systematic review was conducted in alignment with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The databases searched included PubMed, PEDro, and the Cochrane Library (Controlled Trials and Systematic Reviews). After screening, relevant data were extracted, charted, and presented through figures, tables, and narrative synthesis. Only randomized controlled trials examining the effects of acapella or PEP devices in individuals with bronchiectasis were included. Results: This analysis, which included 255 patients from four studies, revealed diverse findings regarding respiratory interventions. The first study found no significant difference in sputum wet weight between bubble-PEP and ACBT during the intervention; however, bubble-PEP demonstrated greater sputum clearance 60 minutes post-session. The second study showed that patients in the OPEP group experienced fewer and later-onset exacerbations compared to those in the CCPT group, along with improvements in health-related quality of life, comfort, and well-being. In the third study, both ELTGOL and Positive Expiratory Pressure techniques led to significant improvements in pulmonary function, with ELTGOL producing superior outcomes. Lastly, the fourth study reported no significant baseline differences in FVC, FEV1, or FEV1/FVC between groups A and B, but both groups showed considerable post-treatment improvements, emphasizing the effectiveness of these interventions in improving respiratory function. Conclusion: These studies highlight that all interventions contribute positively to pulmonary function and quality of life, with techniques like ELTGOL and OPEP showing distinct advantages in areas such as reducing exacerbation frequency and improving long-term sputum clearance. Further research is needed to explore these variations, assess long-term effects, and customize interventions to meet the specific needs of patients with chronic respiratory conditions.